UPAYA MENINGKATKAN KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN TEMATIK MODEL INTEGRATED - Ghina Sakina Muslimawati; Ida Ermiana; Helda Apriani; Lilis Rizkiya Amanda (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This research examines the implementation of Indonesian language learning in the 6th grade at SDN 30 Mataram, focusing on students' listening skills. In the context of integrated learning that combines Indonesian language and Social Sciences (IPS), students engage in activities that enhance language skills through the text